Risk of inn-hospital infection in neonatal care unit - Marta Luján Hernández; Eloida García Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
Background: The newborn present the highest rates of nosocomial infections, which are an alarming challenge in the neonatology units. Objectives: to identify the risk factors of nosocomial infections and to determine the incidence rate of hospital infection in the newborn. Methods: Analytic study of cases and controls of nosocomial infections present in the neonatology service of the Universitary Provincial Hospital of Cienfuegos, from June 2002 to June 2003. Results and Conclusions: The incidence rate of intra-hospital infection was of 4,58 X 100. Children with more than 7 days old have 8,68 times more risk of suffering from that infection than those with less days. The infectious agent that could be isolated was that of Staphylococcus Coagulasa negative (20%).